2020
DOI: 10.1002/anie.202003131
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Benzyne–Phenolate [4+2] Cycloadditions

Abstract: An intramolecular benzyne–phenolate [4+2] cycloaddition is reported. Benzyne precursors, having vicinal halogen‐sulfonate functionalities, linked with a phenol(ate) by various tether groups undergo efficient intramolecular [4+2] cycloaddition by treatment with either Ph3MgLi or nBuLi for halogen–metal exchange to form various benzobarrelenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 76 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In 2005, Danheiser and co-workers reported an intramolecular aryne Diels–Alder reaction with conjugated enynes and arenynes 4-60 , giving rise to highly condensed polycyclic aromatic compounds 4-61 (Scheme a) . Recently, Ohmori, Suzuki, and co-workers demonstrated an intramolecular [4 + 2] cycloaddition of aryne and phenolate by employing o -bromoaryl tosylates as the aryne precursors . In this study, they showed one example with o -silylaryl triflate 4-62 as the precursor and obtained cycloadduct 4-63 in 89% yield (Scheme b).…”
Section: Pericyclic Reactionsmentioning
confidence: 82%
See 1 more Smart Citation
“…In 2005, Danheiser and co-workers reported an intramolecular aryne Diels–Alder reaction with conjugated enynes and arenynes 4-60 , giving rise to highly condensed polycyclic aromatic compounds 4-61 (Scheme a) . Recently, Ohmori, Suzuki, and co-workers demonstrated an intramolecular [4 + 2] cycloaddition of aryne and phenolate by employing o -bromoaryl tosylates as the aryne precursors . In this study, they showed one example with o -silylaryl triflate 4-62 as the precursor and obtained cycloadduct 4-63 in 89% yield (Scheme b).…”
Section: Pericyclic Reactionsmentioning
confidence: 82%
“…108 Recently, Ohmori, Suzuki, and co-workers demonstrated an intramolecular [4 + 2] cycloaddition of aryne and phenolate by employing obromoaryl tosylates as the aryne precursors. 252 In this study, they showed one example with o-silylaryl triflate 4-62 as the precursor and obtained cycloadduct 4-63 in 89% yield (Scheme 27b).…”
Section: Diels−alder Reactionsmentioning
confidence: 84%
“…Suzuki et al reported an intramolecular [4 + 2] cyclization reaction involving a benzyne intermediate in 2020. 85 Employing the iodine group and the sulfonic acid group as benzyne precursors, halogen atom–metal exchange was carried out by n -BuLi to make phenol chain groups rapidly undergo molecular [4 + 2] cycloaddition to access a series of benzo barrelene compounds at 33–99% yield (Scheme 18a). In the same year, Hiyama et al established a new reaction for rapidly constructing naphthyl[2,3- b ]benzofuran compounds from benzyne intermediates with 1,4-disilyl-2-aryloxy-1,3-enynes via sequence catalytic intramolecular hydroarylation, [4 + 2] cycloaddition with a dienophile and oxidative desilylaromatization in one-pot (Scheme 18b).…”
Section: Construction Of Nitrogen-containing Heterocyclic Compounds F...mentioning
confidence: 99%
“…Considered in the beginning as lab curiosities and mechanistic probes, these fleeting species have been enjoying a renaissance in synthetic chemistry over the past two decades. , The breakthrough was the use of 2-(trimethylsilyl)­aryl triflates to generate the strained triple bond systems by a fluoride-induced 1,2-elimination under mild and almost neutral reaction conditions . This invention by Kobayashi paved the way to a wide variety of different reactions, such as various types of cycloadditions, nucleophilic additions, σ-bond insertions, multicomponent reactions, and rearrangements . Common to all of them is that 1,2-bisfunctionalized arenes are obtained as products (Scheme ).…”
Section: Introductionmentioning
confidence: 99%